A Topology Identification and Impedance Estimation Method for Distribution Network with Distributed Generations. Issue 2 (2020) - Zhang, Zhenyu; Li, Yong; Zhang, Jun; Duan, Jing; Cao, Yijia
Abstract: This paper proposes a topology identification and impedance estimation (TIIE) method for the distribution network with distributed generation (DG) units. When the DG unit is connected to the distribution grid, the power injections between the different buses in the distribution grid are no longer independent of each other. This paper demonstrates that the topology identification result has to be corrected when the existing voltage measured based methods are applied to the distribution network involving DG units. To solve the problem, we develop the TIIE method to correct the topology identification error by using the estimation of line impedance. The proposed method does not require any prior knowledge of the network. The case results show a high accuracy on the connectivity identification as well as the estimation of line parameter.